Asionics Philippines, Inc. - Alvarez, Bing; Gilles, Ronald; Martin, Matt; Palana, Jose Marianito (College of Engineering, 1990)
1.1.Findings.The company.Asionics Philippines,Inc. is a semiconductor manufacturing firm.It makes integrated circuits under contract from customers abroad.Because all orders have specifications from the customers,the company is classified as a semi-job shop type of firms.The product.Asionics manufactures four main products which are addressed by their code numbers:Account 02,Account 03,and Account 04.This project study limits itself to only one product-Account 02.The chosen product is a hybrid integrated circuit that is used in home appliances.Production Organization.The one in-charge of production planning is the Production Planning and Control head,Mr. Rudy Ergonia.He is the one who plans the production schedule,the materials requirements plan,manning levels,machine utilization and other related tasks.Mr. Ergonia reports directly to the Production Department head,M. Chito Michael.Forecasting.The company uses forecasting primarily to monitor the materials inventory level.It also it to get an idea of the manning level required.The forecasting tool used is the 3-month simple moving average method.Inventory Management.The company keeps only an inventory of indirect raw materials.All the direct raw materials are provided for by the customer upon order.The materials requirement plan is prepared by the PPC head.Production Scheduling.The head of PPC comes up with a production schedule immediately upon receipt of the order.His inputs are the capacity level and the number of orders.His outputs are the manning level and the distribution and sequencing of machine.Determination of Manning Levels.Based on the prepared production plans,the PPC head comes up with the production.The workers can work overtime or on two shifts.Quality Control.The quality control department monitors the incoming and outgoing of the integrated circuits and outgoing quality of the integrated circuits and the in-process quality.It also issues operator certification.Sampling plans and 100% inspection are used.Preventive Maintenance.The company keeps a small maintenance crew to handle the care and repair of the machines.Most of these workers are casuals.Ergonomic Considerations.Because of the nature of the process,the company's work area is strictly under a dust-free and cool environment.1.2.Recommendations.A.Use a simple exponential smoothing method to force act future demanded.B.Use the priority index method in scheduling orders to aims in production scheduling.The use of Gantt chart and a report list is also recommended to help the PPC head visualized the actual production situation.C.Calculate the theoritical minimum number of workers needed using the forecasted demand with a lead time of one month.D.Increase the number of workers in the maintenance division to assure quicker of machines.